Presidential System Government in the Style of the 1945 Constitution Amendement - Rahma Winny Indahsari; Rana Novita Heryansari; Muhammad Cahya Rahmatullah (Journal of Politics and Policy, 2021)
Indonesia with a presidential system of government that has a characteristic in the form of several characters that make it up. In the notion or presidential system the holder of government power is the president who is separate from the parliamentary institution, the president is the holder of power in the administration of government. This research is a descriptive research with a case study approach. This study contains the researcher's desire to observe and understand how the theory and practice of the presidential government system refers to the basis of the state, namely the 1945 Constitution after the amendment. The results of this study indicate that theoretically the presidential government system is then viewed from the point of view of reality or its application in the form of power sharing. That way it can be seen how the government system if it adopts a presidential system.